Interaction of stroke volume and myocardial phenotype in patients with severe aortic stenosis referred for intervention: outcome data from the BSCMR AS700 study. (8th February 2021) - Thornton, GD; Musa, TA; Rigolli, M; Loudon, M; Chin, C; Pica, S; Malley, T; Foley, JRJ; Vassiliou, VS; Davies, RH; Captur, G; Dobson, LE; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. onbehalf: The BSCMR Valve Consortium Background:  Patients with low-flow aortic stenosis (LF-AS) have higher mortality than those with high-flow severe AS.  The conventional echocardiographic definition of LF-AS is an indexed stroke volume (SVi) <35ml/m2. Whether this cut-off translates to cardiac magnetic resonance (CMR), and how CMR SVi associates with myocardial remodelling (volume/function/scar) and survival is unclear. Purpose:  To determine the association between CMR SVi, myocardial remodelling and survival in severe symptomatic AS.  Methods:   In a multi-centre longitudinal outcome study of patients with severe AS listed for either surgical (SAVR) or transcatheter aortic valve intervention (TAVI) at six cardiothoracic centres, survival was assessed and stratified by SVi. Patients underwent preprocedural echocardiography and CMR between January 2003 and May 2015.  Standardised core-lab analyses on pre-procedural CMR for biventricular volumes, function and scar quantification were performed. All-cause and cardiovascular mortality were tracked for a minimum of two years after AVR. Results:  A total of 674 patients with severe AS (age 75 ± 14years; 63% male, aortic valve area 0.4 ± 0.1 cm2/m2) were included.  Patients with low SVi by CMR <35ml/m2 were older and had a greater burden of comorbidities (atrial fibrillation [AF], diabetes, high BMI). Independent predictors of SVi were age, AF, increased left atrial volume, aortic valve regurgitant fraction and left ventricular mass (LV) mass index (by CMR). There was no difference in SVi with choice of intervention (TAVI vs SAVR) or presence of late gadolinium enhancement. In multivariate analysis (Table 1), SVi was associated with cardiovascular mortality in the whole cohort (HR 0.97, 95%CI 0.95-0.99, p = 0.02), and all-cause mortality after TAVI (HR 0.97, 95%CI 0.95-0.99, p = 0.006) but not SAVR (p = 0.6). Adjusted mortality hazard increases below 50ml/m2 and plateaus between 35-40ml/m2 (Figure 1A), adjusted for LGE, STS score (Society of Thoracic Surgery score) and wall thickness. Conclusion: SVi by CMR is an independent predictor of cardiovascular mortality. Mortality hazard increases progressively below a SVi of 50mL/m2.